2020
DOI: 10.1021/acs.joc.0c00732
|View full text |Cite
|
Sign up to set email alerts
|

Series of Functionalized 5-(2-Arylimidazo[1,2-a]pyridin-3-yl)pyrimidine-2,4(1H,3H)-diones: A Water-Mediated Three-Component Catalyst-Free Protocol Revisited

Abstract: A water-mediated and catalyst-free practical method for the synthesis of a new series of pharmaceutically interesting functionalized 5-(2-arylimidazo[1,2-a]pyridin-3-yl)pyrimidine-2,4-(1H,3H)-diones has been accomplished based on a one-pot multicomponent reaction between arylglyoxal monohydrates, 2aminopyridines/2-aminopyrimidine, and barbituric/N,N-dimethylbarbituric acids under reflux conditions. The salient features of this protocol are avoidance of any additive/catalyst and toxic organic solvents, use of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 60 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…To investigate the greenness and sustainability of the present protocol, a series of green metrics, such as effective mass yield (EMY), atom economy (AE), atom efficiency (AEf), carbon efficiency (CE), reaction mass efficiency, optimum efficiency (OE), and E -factor, for the synthesized compounds were calculated (Supporting Information). The data show that this protocol provides high AE 88.15%–91.95% (for 4a–9d ) and 96.54%–96.73% (for 11a–c ) because only the water molecule is eliminated in this protocol.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To investigate the greenness and sustainability of the present protocol, a series of green metrics, such as effective mass yield (EMY), atom economy (AE), atom efficiency (AEf), carbon efficiency (CE), reaction mass efficiency, optimum efficiency (OE), and E -factor, for the synthesized compounds were calculated (Supporting Information). The data show that this protocol provides high AE 88.15%–91.95% (for 4a–9d ) and 96.54%–96.73% (for 11a–c ) because only the water molecule is eliminated in this protocol.…”
Section: Results and Discussionmentioning
confidence: 99%
“…On the basis of inference revealed from the literature and resultant outcomes, , a plausible mechanistic pathway for the molecular iodine-catalyzed synthesis of imidazo­[1,2- a ]­pyridin-3-yl derivatives 4­(a-o) is depicted in Scheme . The cascade reaction began with the attack of molecular iodine on acetophenone derivatives 2­(a-g) in an aqueous medium followed by dehydration which resulted in situ generation of phenylglyoxal (1′ ) .…”
Section: Results and Discussionmentioning
confidence: 99%
“…On the basis of inference revealed from the literature and resultant outcomes, 41,42 a plausible mechanistic pathway for the molecular iodine-catalyzed synthesis of imidazo[1,2-a]pyridin- undergoes aza-Michael addition to form adduct (6), which subsequently undergoes intramolecular ring closure via an energetically favored 5-exo-trig process, thereby resulting in the cycloadduct (7) followed by removal of water that furnishes the desired product 4(a-o). The whole process involves the elimination of three molecules of water as a greener waste.…”
Section: Resultsmentioning
confidence: 99%
“…Brahmachari et al established an environmentally friendly method for synthesizing a novel series of functionalized pyrimidine derivatives [67]. This method involves a one-pot multicomponent reaction among arylglyoxal monohydrates, derivative of barbituric acid and 2-aminopyridines/2-aminopyrimidine under boiling water (Scheme 3) [67]. The author revealed that no catalyst/other additive was needed and avoided toxic organic solvents.…”
Section: Different Synthetic Strategies Of Pyrimidinesmentioning
confidence: 99%